2017
DOI: 10.4038/agrieast.v10i0.25
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry of cheese ripening

Abstract: Cheese ripening basically includes the breakdown of proteins, lipids and carbohydrates which releases flavour compounds and modifies cheese texture. Principal ripening agents are milk enzymes (plasmin and lipoprotein lipase), milk coagulant, starter lactic culture, secondary culture and ripening agents. The ripening process of cheese is very complex and involves microbiological and biochemical changes to the curd resulting in the flavour and texture characteristics of the particular variety. Microbiological ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…During ripening, SLAB and NSLAB interact with each other and compete for the residual lactose (Blaya et al, 2018). On the other hand, the proteolysis process during the ripening time can lead to the production of metabolites contribute significantly to increase the pH (Pagthinathan & Mohamed Nafees, 2017).…”
Section: Physicochemical and Sensory Propertiesmentioning
confidence: 99%
“…During ripening, SLAB and NSLAB interact with each other and compete for the residual lactose (Blaya et al, 2018). On the other hand, the proteolysis process during the ripening time can lead to the production of metabolites contribute significantly to increase the pH (Pagthinathan & Mohamed Nafees, 2017).…”
Section: Physicochemical and Sensory Propertiesmentioning
confidence: 99%
“…strains to reveal a weak or negative citrate utilization ability, suggesting that the metabolites produced through citrate utilization are not critical contributors to surface-ripened cheese flavors [ 5 , 30 , 42 ]. By contrast, all analyzed strains were able to perform transamination of L-methionine, producing glutamic acid, which together with an amino-acid acceptor, such as α-ketoglutaric acid, constitutes a major contributor to ammonia and other flavor compounds produced in ripened cheeses [ 3 , 30 , 43 , 44 , 45 ]. Moreover, the analysis revealed that the metabolic pathways contributing to cheese sensorial characteristics are strain-dependent [ 41 ].…”
Section: Administration As a Starter Culturementioning
confidence: 99%
“…The changes that occur during proteolysis are based on the concepts of extension and depth, in which the extension index quantifies hydrolysed proteins in high and medium molecular weight (insoluble) peptides and the depth index quantifies those in low molecular weight (soluble) peptides, evaluating the degree of degradation of peptides to amino acids, due to the action of proteolytic enzymes and/or the action of chymosin and plasmin. There are also reactions related to the metabolism of residual lactose by the action of lactic acid bacteria, which synthesise antimicrobial compounds, such as organic acids, which contribute to the microbiological stability and to the development of typical characteristics of matured cheeses (Pagthinathan and Nafees 2015).…”
Section: Maturation Time Identificationmentioning
confidence: 99%